Pengaruh Curah Hujan terhadap Keberhasilan Rukyat Hilal pada Observatorium Lhoknga Aceh - Jafar M. Ali, Machzumy (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2019)
Rukyat hilal of the month of Qamariah, especially the beginning of Ramadan, and Shawwal is a study of falak which often attract attention because of the frequent differences. This is motivated by the uncertainty of rukyat results due to the lack of observable rukyat results. This is one of them caused by the location of the rukyat which is not safe enough from various natural disturbances, such as high rainfall. Lhoknga Observatory Astronomically, this observatory is located at 50 27’ 59, 85” N and 950 14’ 31,87” E, with an altitude of 8 m, and is 15 m from the sea. But from 5 years of observation of the new moon, only one time succeeded in destroying the hilal. The research method uses descriptive analytical methods, collecting data by means of documentation and direct observation. The results of this study found that one of the causes of the low success rate of rukyatul hilal in the observatory was due to its relatively high rainfall which reached an average of 354 mm in years. This rainfall is strongly influenced by the latitude and geographical state of the observatory flanked by the sea and mountains.